Glial cells and energy balance. (January 2017) - Argente-Arizón, Pilar; Guerra-Cantera, Santiago; Garcia-Segura, Luis Miguel; Argente, Jesús; Chowen, Julie A
Abstract : The search for new strategies and drugs to abate the current obesity epidemic has led to the intensification of research aimed at understanding the neuroendocrine control of appetite and energy expenditure. This intensified investigation of metabolic control has also included the study of how glial cells participate in this process. Glia, the most abundant cell type in the central nervous system, perform a wide spectrum of functions and are vital for the correct functioning of neurons and neuronal circuits. Current evidence indicates that hypothalamic glia, in particular astrocytes, tanycytes and microglia, are involved in both physiological and pathophysiological mechanisms of appetite and metabolic control, at least in part by regulating the signals reaching metabolic neuronal circuits. Glia transport nutrients, hormones and neurotransmitters; they secrete growth factors, hormones, cytokines and gliotransmitters and are a source of neuroprogenitor cells. These functions are regulated, as glia also respond to numerous hormones and nutrients, with the lack of specific hormonal signaling in hypothalamic astrocytes disrupting metabolic homeostasis. Here, we review some of the more recent advances in the role of glial cells in metabolic control, with a special emphasis on the differences between glial cell responses in males and females.